Mastery of Science Concepts Improves Scientific Attitude in Elementary School Students - Rajendra Cakra Artaga (Universitas Pendidikan Ganesha, 2021)
Many students have low IPA abilities. Previous research stated that there are still many students who get science learning scores below the average. This study analyzes the relationship between students' scientific attitude and mastery of science concepts in fourth-grade elementary school. This type of research is quantitative research with the correlational method. The research design used is to formulate problems and determine research objectives. The subjects in this study were all students totaling 58 respondents who were taken using the cluster random sampling technique. The method used in this study discusses two variables, the independent variable is students' scientific attitude, and the dependent variable is the mastery of science concepts for grade IV elementary school. The data collection instrument in this study used measurement techniques in 15 formative questions on the dependent variable and 30 questionnaire sheets on the independent variable. Data were analyzed by parametric statistics or product-moment correlation. The results showed differences in the results of students' scientific attitude data with mastery of science concepts. The data showed that tcount was 2,431 > ttable was 1,672 at the significance level = 0.05 with the number of respondents 58 students. Based on these findings, it can be concluded that there is a positive relationship between students' scientific attitudes and mastery of science concepts. Mastery of science concepts can improve students' scientific attitudes.